Computerization of primary health care in Brazil: the network of actors - Ricardo Bezerra Cavalcante; Cristiano José da Silva Esteves; Tarcísio Laerte Gontijo; Maria José Menezes Brito; Eliete Albano de Azevedo Guimarães; Simone de Pinho Barbosa (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: To analyze the network of human and non-human actors involved in the computerization of primary health care in the Brazilian federal government. Method: A qualitative study that used as a theoretical reference the actor-network theory and as a methodological reference the cartography of controversies. Data analysis was carried out using Gephi software, and through the extraction of reports, informed by the actor-network theory. Results: We found a network of 288 connections among 33 actors, composed mainly of nonhuman influencers of computerization. These actors are distributed throughout 3 inter-related communities, and manage the network by defining obligations, penalties, conflicts and intentionalities, thus influencing the success of the intended computerization. Final considerations: The network of actors at the federal level generates situations that, in many cases, hamper the successful implementation of a nationwide computerization strategy.